Specific properties of heavy fraction of mitochondria from human-term placenta - glycerophosphate-dependent hydrogen peroxide production - Honzík, Tomáš; Drahota, Zdeněk; Böhm, Marek; Ješina, Pavel; Mráček, Tomáš; Paul, Jan; Zeman, Jiří; Houštěk, Josef (Placenta, 2006)
Mitochondrial respiratory chain enzyme Complexes are present in placenta at proportion similar to other tissues with exception of glycerophosphate dehydrogenase (mGPDH) which is expressed at a very high rate. As shown by Western blot quantification and respiratory chain enzyme activity measurements, the specific content of mGPDH is similar to that of succinate dehydrogenase or NADH dehydrogenase. Using fluorometric probe dichlorodihydrofluorescein diacetate we found that placental mitochondria display high rate of glycerophosphate-dependent hydrogen peroxide production. This was confirmed by oxygraphic detection of glycerophosphate-induced, KCN- or antimycin A-insensitive oxygen uptake. Hydrogen peroxide production by mGPDH was highly activated by one-electron acceptor, potassium ferricyanide and it was depressed by inhibitors of mGPDH and by cytochrome c. Our results indicate that mGPDH should be considered as an additional source of reactive oxygen species participating in induction of oxidative stress in placenta.
Keywords: financování organizované; Animals; Hydrogen Peroxide; křečci praví; Female; Mitochondria; ženské pohlaví; Placenta; lidé; peroxid vodíku; Reactive Oxygen Species; mitochondrie; Financing, Organized; Oxygen; Oxidoreductases; Glycerolphosphate Dehydrogenase; oxidoreduktasy; reaktivní formy kyslíku; krysa rodu Rattus; zvířata; glycerolfosfátdehydrogenasa; placenta; Rats; kyslík; Cricetinae; Humans